Matrilineality and resistance in Amy Tan’s The Joy Luck Club. - Wee, Jing Yun. (2011)
Amy Tan’s The Joy Luck Club focuses on the matrilineal relationship between two generations of women, four pairs of mothers and daughters. She delves into the complex relationship a girl shares with her mother, and instead of portraying the mother as “the other” as is the case with many texts, the role of the mother is equally foregrounded in the novel. The significance of the mother figure thus emphasizes matrilineality in the novel. In addition to the mother- daughter dialectic, she also explores how this difference between the two generations is expanded by their different backgrounds brought about by the American- Chinese cultural gulf. Throughout the novel, the presence of Chinese myths and sayings is pervasive in the stories the 7 women tell, even present in the lives of the American bred daughters. It is evident then that the stories are a vital connection between the mother- daughter relationships, told in love and hoping that they would embrace their identity as well as learn lessons from their mothers. Therefore this paper explores the matrilineal relations perpetuated by the oratorical traditions passed down from mother to daughter, and also how this tradition negotiates the East- West gulf between them to arrive at an understanding. This paper posits that the mother figure in a displaced Chinese American culture plays an essential role in defining the cultural and gender identity of a Chinese American daughter, and is the only way that these women are able to come into their own and resist the social and cultural forces which have oppressed immigrant women.